Treating acute exacerbations of COPD with Chinese herbal medicine to aid antibiotic use reduction (Excalibur): a randomised double-blind, placebo-controlled feasibility trial - Willcox, Merlin L.; Hu, Xiao-Yang; Oliver, Tom; Thorne, Kerensa; Boxall, Cherish; He, George; Simpson, Catherine; Brotherwood, Becci; O’Neil, Alice; Waugh, Robert; Tilt, Emma; Trill, Jeanne; et al. (Frontiers in Pharmacology, 2023)
Although many acute exacerbations of COPD (AECOPD) are triggered by non-bacterial causes, they are often treated with antibiotics. Preliminary research suggests that the Chinese herbal medicine "Shufeng Jiedu" (SFJD), may improve recovery and therefore reduce antibiotic use in patients with AECOPD.To assess the feasibility of conducting a randomised placebo-controlled clinical trial of SFJD for AECOPD in UK primary care.GPs opportunistically recruited patients experiencing an AECOPD. Participants were randomised 1:1 to usual care plus SFJD or placebo for 14 days. Participants, GPs and research nurses were blinded to treatment allocation. GPs could prescribe immediate, delayed or no antibiotics, with delayed prescribing encouraged where appropriate.Participants were and asked to complete a participant diary, including EXACT-Pro and CAT TM questionnaires for up to 4 weeks. Outcomes included recruitment rate and other measures of study feasibility described using only descriptive statistics and with no formal comparisons between groups. We also conducted qualitative interviews with recruited and non-recruited COPD patients and clinicians, analysed using framework analysis.Over 6 months, 19 participants (6 SFJD, 13 placebo) were recruited. Sixteen (84%) participants returned diaries or provided a diary by recall. Overall, 1.3 participants were recruited per 1000 patients on the COPD register per month open. Median duration of treatment was 9.8 days in the intervention group vs. 13.3 days in the placebo group. The main reason for discontinuation was perceived side-effects in both groups. Point estimates for both the EXACT-PRO and CAT TM outcomes suggested possible small benefits of SFJD. Most patients and clinicians were happy to try SFJD as an alternative to antibiotics for AECOPD. Recruitment was lower than expected because of the short recruitment period, the lower incidence of AECOPD during the COVID-19 pandemic, patients starting antibiotics from "rescue packs" before seeing their GP, and workforce challenges in primary care.Recruitment was impaired by the COVID-19 pandemic. Nevertheless, we were able to demonstrate the feasibility of recruiting and randomising participants and identified approaches to address recruitment challenges such as including the trial medication in COPD patients' "rescue packs" and delegating recruitment to a central trials team.